The Impact of Minimum Wages on Employment: Evidence from a Lower Middle-Income Country - Cuong Viet Nguyen (Global Labor Organization (GLO), 2023)
In this study, we examine the impact of minimum wages in Vietnam using individual-level data from the 2012-2020 annual Labor Force Surveys. During this period, the average real minimum wage increased by around 4% per year. Overall, we do not find significant effects from minimum wages on employment and monthly wages. However, we find a considerable negative effect on workers' total working hours. Working hours per week are reduced by 0.38% for a 1% increase in the minimum wage. Since total wages remain unchanged, a reduction in working hours results in an increase in hourly income. A 1% increase in the minimum wage leads to a 0.32% increase in hourly wages. Interestingly, for workers earning below minimum wage, we find a positive effect from minimum wages on their monthly income. A 1% increase in the minimum wage increases monthly income of workers earning below minimum wage by 0.83%.
Keywords: J31; J50; O12; 330; Minimum wages; employment; labor productivity; impact evaluation; Vietnam